Weibull Strength Analysis of Pineapple Leaf Fiber - Charlie, Chin Voon, Sia; J.S.Y., Wong; S.K, Thangavelu; K.H., Chong; Annie, Joseph (Trans Tech Publications Ltd, Switzerland, 2021)
Pineapple leave fiber (PALF) can be considered as one of the green materials to the industries, which is the potential to replace the non-renewable synthetic fiber. However, the high disparity in the mechanical properties of PALF becomes an issue in structural composite design. Hence, improved Weibull distribution is utilised to quantify the tensile strength variation of PALF in various gauge lengths. The single fiber tensile test was performed after the fiber surface treatment and fiber diameter scanning. The predicted PALF strength by applying the improved Weibull distribution incorporating with conical frustum model is well compromised with experimental data compared to the traditional Weibull model.